PENGEMBANGAN ENSIKLOPEDIA PERALATAN DAN BAHAN LABORATORIUM BIOLOGI SEBAGAI SUMBER BELAJAR SMA NEGERI 8 PONTIANAK - Selviana Lilis; Kurnia Ningsih; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The aimed of this research were to know the appropriateness and to know students response of encyclopedia equipments and materials on biology laboratory as learning source to tenth grade students of SMAN 08 Pontianak. The methodology of this research was research development especially following Borg and Gall Model. The stages of this research are research and information collecting, planning, develop preliminary form of product, preliminary fieled testing, main product revision, main field testing, and operasional product revision. This research was held on SMAN 8 Pontianak. The sample of this research was 12 students for preliminary fieled testing and 35 students for main field testing. The tools of data collection in this research were encyclopedia validation sheet and students questionaire. The research findings showed that content validity index score of encyclopedia equipments and materials of biology laboratory was 0.99 and it is categorized as valid. It showed that encyclopedia is fit for use as learning source on sub work safety material to tenth grade students. While, the research result of students response on preliminary and main test were 85.36% and 85.81%. these are categorized as very strong. As the result, it could be concluded that encyclopedia equipments and materials is fit for use as learning source on sub work safety material with strong response from students. Keywords: Encyclopedia, Learning Source, Students Response, Sub Work Safety Material